Pemaksaan Perkawinan Korban Dengan Pelaku Pemerkosaan - Zahra, Fannia Al; Senjaya, Oci (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2023)
Legal systems around the world must provide effective protection for victims of rape and forced marriages. This includes ensuring that perpetrators are fairly processed and punished, and that victims receive the help and support they need to restore their health and safety. This study aims to determine the form of legal protection given to rape victims and efforts to avoid the practice of marrying rape victims to perpetrators. Scientific activities carried out are based on methods and systematics to get answers to the problems faced, so appropriate research methods are needed, the method used for this type of research is normative juridical. The nature of this research is perspective. Research with this type of perspective aims to get suggestions to solve a problem systematically. The approach used is a conceptual approach, which is derived from the ideas and thoughts of the doctrinal developments in the science of law.